Characterization and analysis of nanostructured CdO thin film using LIBS technique - Tawfik, Walid; Farooq, W Aslam; Alahmed, Zeyad A.; Sarfraz, M.M.; Ahmad, Kaleem; Yakuphanoğlu, Fahrettin (My University, 2013)
Nanostructured thin films of cadmium oxide (CdO) have been synthesized using sol-gel technique on slide glass substrates. Thickness of the film is about 250 nm with average grain sizes of CdO in the range of 93-250 nm. Laser induced breakdown spectroscopy (LIBS) is used to investigate the synthesized CdO thin film. We have investigated LIBS spectrum of CdO thin film in air atmosphere using Spectrolaser-7000 system with 100 mJ fundamental laser beam from Nd:YaG laser and varied delay times from 200 ns to 2 microseconds. Many atomic and ionic lines of Cd were resolved and the variation with the delay time was studied. The plasma parameters have also been studied for Cd 508.58 nm. It is found that plasma cooled very fast after 500 ns as compared to the bulk material. The later showed that the recombination processes are growing very fast with time for nanostructured CdO thin film. © 2013 IEEE.
2013 Saudi International Electronics, Communications and Photonics Conference, SIECPC 2013 -- 27 April 2013 through 30 April 2013 -- Riyadh -- 98388
Keywords: Cadmium oxide; Electron density; Laser spectroscopy; Plasma temperature; Thin film